Teknik Pembesaran Udang Vaname (Litopenaeus vannamei) di Kolam HDPE oleh Kelompok Budidaya Ikan Mina Bangkit Bersama Karangrejo, Banyuwangi - Vicky Adi Pratama; Ferdy Niko Agustin; Ryo Al Fandi; Alya Hafizh Pabo; M. Fahmi Dimas Prayogi; Lauren Nadia Nur’andiaz (Lembaga Pengembangan Kinerja Dosen, 2025)
Field Work Practice (PKL) at Tambak Mina Bangkit Bersama (MIBAMA), Karangrejo, Banyuwangi, was conducted from June 26 to August 3, 2024, with the aim of understanding the process of growing Litopenaeus vannamei shrimp in HDPE ponds. Vaname shrimp farming involves pond preparation, seedling stocking, feed management, and water quality monitoring to optimize shrimp growth. Growth monitoring was carried out through sampling, resulting in an Average Daily Growth (ADG) value ranging from 0.41 to 0.71 grams per day. Water quality measurements showed that temperature, pH, and dissolved oxygen levels were still within safe ranges, although several parameters such as salinity, TDS, and ORP required special attention. Partial and total harvesting resulted in an accumulated production of 5.1 tons in this cycle. The use of HDPE ponds proved effective in maintaining the aquaculture environment and supporting production intensification. This study emphasizes the importance of proper water and feed quality management to enhance shrimp productivity and health, while also providing recommendations for continuous monitoring to address stress factors in shrimp during cultivation.